Safety, tolerability, and pharmacokinetics of single‐ and multiple‐dose administration of islatravir (MK‐8591) in adults without HIV - Randolph P. Matthews; Wendy Ankrom; Evan Friedman; Deanne Jackson Rudd; Yang Liu; Robin Mogg; Deborah Panebianco; Inge De Lepeleire; Magdalena Petkova; Jay A. Grobler; Selwyn Aubrey Stoch; Marian Iwamoto (Wiley, 2021)
Abstract Islatravir (MK‐8591) is a nucleoside analogue in development for the treatment and prevention of HIV‐1. Two phase 1 trials were conducted during initial evaluation of islatravir: rising single doses (Study 1) and rising multiple doses (Study 2) of oral islatravir in male and female participants without HIV (aged 18-60 years). Safety, tolerability, and pharmacokinetics of islatravir (plasma) and islatravir‐triphosphate (peripheral blood mononuclear cells) were assessed. In Study 1, 24 participants, assigned to 1 of 3 panels, received alternating single doses of islatravir in a fasted state from 5 mg to 400 mg, or placebo, over 3 dosing periods; a 30 mg dose was additionally assessed following a high‐fat meal. In Study 2, 8 participants per dose received 3 once‐weekly doses of 10, 30, or 100 mg islatravir or placebo in a fasted state. For each panel in both trials, 6 participants received active drug and 2 received placebo. Islatravir was generally well‐tolerated, with no serious adverse events or discontinuations due to adverse events. Islatravir was rapidly absorbed (median time to maximum plasma concentration 0.5 hours); plasma half‐life was 49-61 h; intracellular islatravir‐triphosphate half‐life was 118-171 h. Plasma exposure increased in an approximately dose‐proportional manner; there was no meaningful food effect. There was a modest degree of intracellular islatravir‐triphosphate accumulation after multiple weekly dosing. After single oral doses of islatravir greater than or equal to 5 mg, intracellular islatravir‐triphosphate levels were comparable to levels associated with efficacy in preclinical studies. These results warrant continued clinical investigation of islatravir.